A critical review of biomonitoring in East African rivers: fostering community-based collaboration for environmental change observation - Kitaka, Nzula; Omondi, Lorine A.; Mureithi, Priscilla W.; Bauer, Andreas; Melcher, Andreas; Ssanyu, Grace A. (Frontiers in Water, 2024)
The contribution of citizen scientists in environmental monitoring is notably increasing significantly. Governments worldwide establish Water Users Associations (WUAs) as a good practice model, to implement Integrated Water Resource Management (IWRM) at local levels.These associations target different stakeholders depending on the expected outcome. However, their effectiveness especially in East Africa can only be determined case by case. In Kenya, Water Resources Users Associations are registered, voluntary community groups whose members are water users and land owners. Similarly, in Uganda community-based initiatives exist, especially along degraded rivers, involving cooperation between local communities and regional water authorities. Contrary, it has been reported that in Tanzania many community initiatives created become non-functional within two to three years of induction. In general, the main responsibilities of Water Users Associations or its equivalent is to manage and conserve water resources for sustainable uses. In most cases, water quality monitoring by communities through citizen science is limited to the visual appearance of water in the river channel. While this can indicate the water's aesthetic value, it is insufficient for assessing the ecological status of rivers, which is influenced by a variety of physical, chemical, biological, and socio-economic factors. The use of bioindicators has been advocated as a feasible method for community-based water quality river monitoring.Therefore, this review explores the commonly used bio-indicators and bio-assessment tools for river health assessment and their complexities when using a biomonitoring community-based approach through citizen science. Tolerance and intolerance macroinvertebrate and fish metric protocols that utilize identification keys has been recommended. These protocols are designed to be user-friendly and require minimal taxonomic expertise, making them easy to use by community volunteers with minimal basic training. The sustainability of these citizen science initiatives relies on the motivation of volunteers, the frequency of monitoring activities, and collaboration with researchers and government agencies. These initiatives not only facilitate environmental monitoring but also foster community engagement and awareness regarding the ecological status of rivers, thereby addressing knowledge and data gaps necessary for effective policy-making. This approach provides a practical model for environmental stewardship and participatory resource management in East Africa.